PARPA II – Relatório de Avaliação de Impacto Pesquisa Sobre o Combate À Corrupção - CS Advocacia, Consultoria e Serviços (Republica de Moçambique: Ministério da Planificação e Desenvolvimento, 2009)
Este estudo enquadra‐se no âmbito dos Mecanismos e Instrumentos de Monitoria e Avaliação do Plano de Acção para a Redução da Pobreza Absoluta 2006‐2009 (PARPA II), que preconizam a preparação de um Relatório de Avaliação de Impacto (RAI). O RAI tem como objectivo sintetizar informação sobre a pobreza e a evolução de indicadores socioeconómicos e analisar esta informação com uma visão particular para atribuir causa e efeito. Como parte das prioridades do PARPA II, o combate à corrupção é um dos temas a ser abordado no RAI. Neste âmbito, o presente estudo tem como objectivo geral, avaliar o impacto das medidas adoptadas no âmbito do combate à corrupção, com enfoque nos mecanismos de controlo interno (inspecções e auditorias), relacionando com a quantidade e qualidade dos recursos humanos existentes, o desempenho e impacto do Gabinete Central de Combate à Corrupção (GCCC).
Keywords: #Policy Document / Documento de Política; G - Mozambique / Moçambique; L - portuguese / português; corruption / corrupção; government policy / politica governamental

Capacity Strengthening in the Least Developed Countries (ldcs) for Adaptation to Climate Change (clacc): Climate Change and Health in Mozambique - Bambaíge, Albertina João; Cuamba, Boaventura; Hauengue, Maria dos Anjos (International Institute for Environment and Development (IIED), 2008)
The relationship between climate change and its effects on human health has been widely studied. Increases in temperature and variations in precipitation can exacerbate a number of human diseases including respiratory infections, malnutrition, vector and water borne diseases such as malaria and cholera. Besides all efforts undertaken by the Mozambican Government to reduce poverty and meet the MDGs targets, it is clear that climate change effects will influence negatively in meeting these targets. Damages caused by floods in Mozambique undermine economic growth rates of the country. Mainstreaming climate change adaptation into government policies would strengthen the capacity of the country to deal with climate change impacts. Climate change is a reality and the impacts on health are great with the poor at most risk. Efforts must be done nationally at all levels to come up with a proactive approach since all actors in the Mozambican society are directly or indirectly affected. This must include clear policies and strategies to deal with impacts of climate change on health; intersectoral approaches for strengthening the implementation of these policies and a greater support from those wealthy in resources and knowledge for minimizing the risks and increase community's adaptation capacity. The case study included in this country report highlights the relationship between climate change and human health through an analysis of malaria and cholera data taking the example of the 2000/2001 floods, which were considered the worst in the last fifty years. Adaptation practices and the adaptive capacity of the country during floods periods, policies and strategies are also discussed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; climate change / mudanças climáticas; government policy / politica governamental; health / saúde; institutions / instituições; natural disasters / desastres naturais

Plano De Acção Para a Redução Da Pobreza Absoluta: 2006-09 (PARPA II) - República de Moçambique (República de Moçambique, 2006)
O Plano de Acçãoo para a Redução da Pobreza Absoluta para 2006-2009 (PARPA II) do Governo de MoÁambique tem em vista alcanÁar o objectivo de diminuir a incidÍncia da pobreza de 54% em 2003 para 45% em 2009. Este documento sucede ao PARPA I de 2001-2005 (Governo de MoÁambique, 2001), mantendo em comum as prioridades em ·reas do desenvolvimento do capital humano na educaÁ„o e sa˙de, da melhoria na governaÁ„o, do desenvolvimento das infra-estruturas b·sicas e da agricultura, do desenvolvimento rural, e de melhoria na gestão macro-económica e financeira. O presente PARPA distingue-se do anterior por incluir nas suas prioridades uma maior integração da economia nacional e o aumento da produtividade. Em particular, focaliza a atenção no desenvolvimento de base ao nÌvel distrital, na criação de um ambiente favorável ao crescimento do sector produtivo nacional, melhoria do sistema financeiro, ao florescimento das pequenas e mÈdias empresas enquadradas no sector formal, e a desenvolver ambos os sistemas de arrecadaÁ„o de receitas internas e de afectação dos recursos orçamentais.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; poverty / pobreza

PPFD/PRODER Joint Review and Strategy Proposal for the National PPFD Program Architecture - Final report - Ministry of Planning and Development - Mozambique (MÉTIER, Consultoria e Desenvolvimento, Lda, 2006)
The present report integrates the main conclusions of the three PPFD projects evaluation: PPFDNorth, PPFD-Centre and PRODER, establishing the articulation with the evolution of the political and administrative evolution and relevant for the decentralization process. Based on this analysis the report proposes the architecture of a single National PPFD Program and its main components. This report is based on the main conclusions of an extensive field work covering various provinces and districts and of the various workshops with participation of representatives of the Government at different levels, of the partners and national and international staff from the projects. It constitutes an important basis for the work of the commissions created to start the program formulations. This final report is complemented by other four partial reports: Evaluation report of the PPFD North; Evaluation report of the PPFD Centre; Evaluation report of the PRODER; and Phases 2 and 3 Report: Strategy for a single national PPFD
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; government policy / politica governamental